Standardized Diagnostic Workup and Patient-Centered Decision Making for Surgery and Neck Dissection Followed by Risk-Factor Adapted Adjuvant Therapy Improve Loco-Regional Control in Local Advanced Oral Squamous Cell Carcinoma - Wichmann, Gunnar; Pavlychenko, Mykola; Willner, Maria; Halama, Dirk; Kuhnt, Thomas; Kluge, Regine; Gradistanac, Tanja; Fest, Sandra; Wald, Theresa; Lethaus, Bernd; Dietz, Andreas; Wiegand, Susanne; et al. (Frontiers in Oncology, 2021)
Background: Standardized staging procedures and presentation of oral squamous cell carcinoma (OSCC) patients in multidisciplinary tumor boards (MDTB) before treatment and utilization of elective neck dissection (ND) are expected to improve the outcome, especially in local advanced LAOSCC (UICC stages III–IVB). As standardized diagnostics but also increased heterogeneity in treatment applied so far have not been demonstrated to improve outcome in LAOSCC, a retrospective study was initiated. Methods: As MDTB was introduced into clinical routine in 2007, 316 LAOSCC patients treated during 1991-2017 in our hospital were stratified into cohort 1 treated before (n=104) and cohort 2 since 2007 (n=212). Clinical characteristics, diagnostic procedures and treatment modality of patients was compared using Chi-square tests and outcome analyzed applying Kaplan-Meier plots and log-rank tests as well as Cox proportional hazard regression. Propensity scores (PS) were used to elucidate predictors for impaired distant control (DC) in PS-matched patients. Results: Whereas the distribution in treatment modalities applied showed insignificant alteration, the surgical treatment included significantly more often resection of the primary tumor plus neck dissection, tracheostomy and percutaneous endoscopic gastrostomy tube (PEG) use. We observed significantly improved local (LC) and loco-regional control (LRC) but impaired DC after 2006. Only insignificant improved disease- (DFS), progression- (PFS) and event-free (EFS) as well as tumor-specific (TSS) and overall survival (OS) were found. Conclusions: Despite standardized diagnostic procedures, decision-making considering clear indications and improved therapy algorithms leading to improved LC and LRC, only slightly improved TSS and OS were seen probably related to impaired DC.